Ammonia and Total Nitrogen Removal Using Equisetum hymale Based Phytoremediation in Landfill Leachate - Maria Ulfah; Lilla Panca Faizsyahrani; Sumarno Sumarno; Angelica Tricia Wijaya (Jurnal Penelitian Pendidikan IPA, 2025)
In line with the problems faced by all landfills in Indonesia, the high level of waste entering landfills is not commensurate with the cost and quality of waste management which is still low. The volume of landfill leachate with levels of organic, inorganic and metal content at the Jatibarang landfill has the potential to pollute the Kreo river. The dangerous impact on health and ecosystem continuity if the total ammonia and nitrogen content is too high in Jatibarang landfill leachate, efforts to manage it with a phytoremediation agent are Equisetum hymale. This research method is an experiment with a completely randomized design (CRD) designed with the type of Equisetum hymale and 3 treatment of Equisetum hymale biomass, namely, P0: 0 g, P1: 750 g, and P2: 1000 g of Equisetum hymale per 10 liters of leachate, each treatment was repeated 3 times. This phytoremediation is very effective in reducing ammonia levels, the reduction in ammonia levels reached 99.7% and the highest total nitrogen content reached 91.7%. It was concluded that the Equisetum hymale was effective in reducing ammonia levels. The effectiveness of reducing ammonia levels and nitrogen levels was most optimal on the third day of P2. The Equisetum hymale removed ammonia and total nitrogen up to 70% in variation of contact time.